THE RIGHT TO A HOME IN THE CASE-LAW OF ECHR VS. THE RIGHT TO A HOME IN THE CASE-LAW OF CROATIAN COURTS - Bodul, Dejan (EU and comparative law issues and challenges series (ECLIC), 2018)
The legal concept of the “right to a home” reflects the principle of social solidarity. It is rooted in modern philosophical and theoretical humanistic school of thought, but also in the secular sense of avoiding social Darwinism. Nevertheless, this principle can, as any other, turn into its own opposite. Its realisation can also result in consequences that challenge its meaning. However, this does not diminish its value. The emphasis here is on the modalities of its application. Therefore, the author shall analyse the practice of the European Court of Human Rights (hereinafter: ECHR) in proceedings concerning the right to a home and its implementation in the Croatian legal system. He assumes that these findings could be a key to understanding the subject of the paper based on ECHR case-law. The complexity of the research topics and the set tasks of this paper determined the choice of methods. Consequently, the author used normative legal methodological approach in the analysis. It is important to note that the scope of this paper does not allow for a detailed analysis of this topic; we are therefore forced to limit our analysis exclusively to some aspects/issues of the new enforcement legislation.